STUDY ON THE ANTIBACTERIAL ACTIVITY OF BERGENIA PURPURASCENS EXTRACT - Shi, Xiaoli; Li, Xu; He, Jing; Han, Yingmin; Li, Suhua; Zou, Ming (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Bergenia purpurascens has tonic, haemostatic and anti-tussive actions. Anti-inflammatory and anti-bacterial activities of Bergenia purpurascens have not been reported so far. The objective of this paper is to provide experimental basis for the clinical application of Bergenia purpurascens through the pharmacodynamic study on its anti-inflammatory and anti-bacterial effects. Methods: Experimental models of xylene-induced ear edema in mice, cotton pellet granuloma in rats, and acetic acid-induced peritoneal capillary permeability in mice were used to investigate the anti-inflammatory effect of Bergenia purpurascens; bacteriostatic and bactericidal effects of Bergenia purpurascens extract on Staphylococcus aureus (SA), methicillin-resistant Staphylococcus aureus (MRSA), and β-lactamase positive Staphylococcus aureus (ESBLs-SA), were observed in vitro. Results: The results show that Bergenia purpurascens extract could markedly inhibit xylene-induced mouse ear edema, cotton pellet granulation tissue hyperplasia, and increased capillary permeability. Bergenia purpurascens extract has an inhibitory effect on SA, MRSA and ESBLs-SA. Conclusion: We conclude that Bergenia purpurascens extract has certain anti-inflammatory and anti-bacterial effects.